Biodiesel production from waste cooking oil using calcium oxide/nanocrystal cellulose/polyvinyl alcohol catalyst in a packed bedreactor - Zik, Nor Azyan Farrah Adila; Sulaiman, Sarina; Jamal, Parveen (Elsevier Ltd, 2020)
In this study, biodiesel was synthesized from a reaction of waste cooking oil (WCO) and methanol in the presence of catalyst which was derived from chicken bone and coconut residue in a packed bed reactor. Calcium oxide (CaO) was extracted from calcined chicken bone and nano-crystal cellulose (NCC) was isolated from coconut residue by acid hydrolyzed and were supported with polyvinyl alcohol (PVA). The catalyst was analyzed using Fourier transform infrared (FTIR), Field emission scanning electron microscopy (FESEM), Thermogravimetric analysis (TGA) and X-ray diffraction (XRD) to study its elemental composition and surface morphology. The parameters used for the reaction were optimized by Design of Experiment (DOE) using Central Composite Design (CCD) to maximize the biodiesel yield. The maximum yield of 98.40% was obtained at optimum temperature, methanol to oil and catalyst loading of 65 C, 6:1 and 0.5 wt%, respectively. Investigation on the kinetic of the reaction specified that the reaction followed pseudo first order reaction with k-value ranged from 0.0092 min1 to 0.0151 cm1 and Thiele modulus was less than 2. The activation energy Ea for the transesterification reaction was 45.72 kJ/mol.